PENERAPAN COOPERATIF LEARNING TIPE TWO STAY-TWO STRAY PADA MATERI PERBANDINGAN - Nursiasari, Dwi; Halini, Halini; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aimed to determine the effectiveness of the implementation of Two Stay-Two Stray type as learning model in teaching comparison in the Class VII students of â€œSMPN 03 KUBU RAYAâ€. The research method used was pre-experimental method with one-shot case study design. The aspect to determine the effectiveness of this research are class management, students activity and studentâ€™s outcomes. The tools of data collecting were 4 iteams essays, teacherâ€™s class management and studentsâ€™ activities observational sheets. Through descriptive analysis, founded that the result of teachersâ€™ class management was categorized as good (3,4), while the studentsâ€™ activities result categorized as active (73,3%) and studentâ€™s completeness not fulfilled classically (only 19 students or 59,3% of students can fulfill the standard completeness). Two Stay-Two Stray Â type as learning model in teaching comparison in the class VII Â students of â€œSMPN 03 KUBU RAYAâ€ is effective on the aspects of class management and students activity.Â Keywords: Comparison, Effectiveness, Two Stay-Two Stray type Of Cooperative ModelÂ